1995
DOI: 10.1111/j.1468-2958.1995.tb00368.x
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis Summarizing the Effects of Pornography II Aggression After Exposure

Abstract: This meta-analytic revipW examines the effect that exposure to pornography produces on aggressive behavior under lnboratoy conditions considering a variety ofpossible moderating conditions (level ofsexual arousal, level of prior anger, type of pornography, gender of subject, gender of the target of aggression, and medium used to convey the material). The summa y demonstrates a homogeneous set of results showing that pictorial nudity reduces subsequent aggressive behavior, that consumption of material depicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
146
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(156 citation statements)
references
References 78 publications
7
146
1
2
Order By: Relevance
“…A meta-analysis suggested that depictions of sexual activity increased reactive aggression in men and women (but that nudity alone decreased aggression) (Allen, D'Alessio, & Brezgel, 1995). Explanations for these findings were mostly based on the assumption of excitation transfer: Sexually induced arousal was functionally equivalent to angerinduced arousal and thus hypothesized to have a similar effect.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis suggested that depictions of sexual activity increased reactive aggression in men and women (but that nudity alone decreased aggression) (Allen, D'Alessio, & Brezgel, 1995). Explanations for these findings were mostly based on the assumption of excitation transfer: Sexually induced arousal was functionally equivalent to angerinduced arousal and thus hypothesized to have a similar effect.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, several meta-analyses have concluded that there are reliable associations between pornography consumption and sexual aggression; however, the evidence for the causal relationship remains equivocal (Allen et al, 1995;Malamuth et al, 2000;Seto et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…In Allen et al (1995)'s meta-analysis involving 33 studies and 2,040 participants, exposure to violent pornography, and nonviolent pornography to a lesser degree, were found to facilitate aggressive behaviour in men and women; exposure to nonpornographic nudity, however, diminished aggressive behaviour. Interestingly, the finding that nonviolent pornography facilitated aggressive behaviour in women, who engage in aggression to a lesser degree than men, indicates that the Excitation Transfer…”
Section: Pornographymentioning
confidence: 99%
See 2 more Smart Citations